Depression and creativity: the case of the german poet, scientist and statesman J.W.v. Goethe - Holm-Hadulla, Rainer M.; Roussel, Martin; Hofmann, Frank-Hagen (Journal of affective disorders, 2010)
Background - Goethe was one of the most creative poets, scientists and statesmen ever existing. Since the age of fourteen, he suffered from severe mood swings. His descriptions of feelings, emotions, and mental states related to temperamental and poetic melancholy, depressive episodes, dysthymic phases, and creativity are unique in respect to their phenomenological precision and richness. Furthermore, his (self-) therapeutic strategies and his self transformation in literature remain interesting until today for psychopathology, psychotherapy and creativity research. - Methods - Goethe's self-assessments in his works and letters as well as the description of him by others are analysed by phenomenological and hermeneutic methods from the perspective of current psychiatric classification and psychotherapeutic knowledge. - Results - From a modern scientific perspective Goethe's mood swings are not to be regarded as expressions of a “poet's melancholy” in fashion at his time but as symptoms of depressive episodes. Several distinctive depressive episodes can be diagnosed which were characterized by long lasting depressive mood, lack of drive, interests and self-esteem combined with social retreat and physical illness. Moreover, Goethe described a mood disorder which fits into the modern concept of “driven dysthymia” or Bipolar II disorder. Goethe's depressive moods were associated with eminent poetic creativity whereas in times of scientific and political productivity Goethe seemed to be protected against depressive episodes. - Limitations - Phenomenological and hermeneutic analysis cannot offer causal explanations but only reasons for understanding and communicative action. - Conclusions - In Goethe's life poetic incubation, illumination and elaboration seemed to be associated with psychic labilisation and dysthymia, sometimes with depressive episodes in a clinical sense. Thus, creative work was on the one hand triggered by depressive and dysthymic moods and served on the other hand to cope with depressive moods as well as with suicidal tendencies. In line with modern empirical results Goethe's scientific and social activities and achievements were associated with personal well-being, but also with lack of poetic inspiration.